A Comparative Study of Void Distribution Pattern on the Strength Development between OPC-Based and Geopolymer Concrete. (5th November 2019) - Nazari, Ali; Bagheri, Ali; Sanjayan, Jay; Yadav, Parth N. J. A.; Tariq, Hasnat
Abstract : The correlation between the void structure, as a representative of bleeding behaviour, and the strength of concrete is investigated in the current article. Early age cracking, due to dry shrinkage, can negatively influence the durability of pavement structures. Also, dry shrinkage of concrete is directly proportional to the bleeding rate. Thus, modifying the bleeding rate reduces the early cracking that happens in hardened concrete. Geopolymer concrete is presented as a suitable material for the replacement of Ordinary Portland Cement (OPC). Geopolymers have shown superior bleeding behaviour to that of OPC concrete and can be substituted for paving by means of increasing the durability. This research has used section image analysis and rebound hammer techniques to create a relationship between the void structure and the strength of concrete. Mixtures are prepared by 10% substitution of the iron-making slag to study the effects of slag on the bleeding rate. Also, the influence of water-to-binder ratio on the void structure and strength development is studied. The results indicate that the void volume has an indirect correlation to the strength development of normal concrete, while the addition of slag makes it reverse. Geopolymer concrete shows less bleeding than OPC concrete, making it a suitable alternative for pavement. It is also concluded that the replacement of slag in concrete enhances the bleeding rate and durability.